Infection and microleakage the caused of endodontic failure - Achiar, Kurniasri Amas; Subrata, Gantini (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2008)
The success of endodontic treatment depends on the quality of endodontic treatment and the final restoration. The mean reason for endodontic treatment failure is usually microleakage. That is why it becomes one of the priorities for dental research to prevent microleakage. Infection during the root canal treatment can be prevented. First, by employing strict aseptic clinical techniques follows by cleaning all bacteria and preoperative necrotic pulp-tissue remnants from the root canal. Irrigants are essential in this phase. The shaping of the canal is also an important prerequisite for endodontic success. Removal of the smear layer can enhance seal ability. Second, obturation of the root canal should leave the tooth in the most biological inert condition possible, and it must prevent reinfection as well as the growth of any microorganisms remaining in the canal. The application of an antibacterial dressing between appointments is absolutely necessary or the root canal has to be obturated at the first appointment in order to deprive the microorganisms of nutrients and space to multiply. The temporary filling must be at least 3.5 mm thick. Failure occurs because of missed canals, iatrogenic events and radicular fractures have to be avoided. At the end, clinicians have to confirm that the root canal is cleaned and hermetically obturated because hermetic root canal filling will prevent the leakage of an irritant to the apical area.